Effectiveness of Playing Origami Intervention on Improvement of Fine Motor Development Pre School Children - Harsismanto J1 , Larra Fredrika1, Novia Wati2 , Padila3 , Desri Suryani4 , Yandrizal5 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: One aspect of development in children is fine motor development. Delays in fine motorskills can make children have difficulty exploring the environment, barriers to learning, lazy writing, lackof creativity. This study aims to determine the effectiveness of playing Origami interventions to improvepreschool children’s fine motor skills in PAUD Aisiyah VI Bengkulu City.Study Design:This research is a Quasi-Experimental study with a research design of “one group pretestand post-test without control group design”, a sample of 26 preschool children using purposive sampling.The intervention was given for two weeks as many as six meetings with 30 minutes per session. Data onchildren’s fine motor development were collected using the DDST II screening format.Results: Analysis using the Wilcoxon test obtained ? value 0.000 (? 0.05). In conclusion, Origami playintervention is statistically effective in improving the fine motor skills of preschool children.Conclusion: Teachers and parents should pay more attention to and increase the stimulation of preschoolchildren’s fine motor skills by facilitating children to play folding, sticking, and paper cutting more often.